Inovasi media penyuluhan pertanian berbasis smartphone menggunakan aplikasi Glide App di BPP Junrejo Kota Batu - Nur Aisyah; Yudi Rustandi; Sabir (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2026)
Agricultural extension at Balai Penyuluhan Pertanian (BPP) Junrejo still faces limitations in time, human resources, field coverage, and the use of smartphones as learning media. This study aimed to develop and evaluate Agro Tani, a smartphone-based agricultural extension medium created with the Glide App. The study used Research, Development, and Diffusion (RD&D) with the 4D development model: define, design, develop, and disseminate. The research was conducted at BPP Junrejo, Batu City, from January to February 2026, involving 20 respondents, comprising 11 extension workers and 9 farmers, selected through saturated sampling. Data were collected through observation, interviews, questionnaires, pre-test and post-test instruments, skill assessment, and user satisfaction evaluation. Data were analysed descriptively, using N-Gain and the Wilcoxon Signed-Rank Test. The developed application provided several functions, including extension materials, images and videos, review and rating, BPP Junrejo information, BPP Centre, location access, and external information links. Evaluation showed a high knowledge improvement (N-Gain = 0.84), moderate skill improvement (N-Gain = 0.32), very high user satisfaction (score = 853), and very effective training implementation (N-Gain = 0.81). Wilcoxon analysis showed significant differences between pre-test and post-test scores for knowledge, satisfaction, and skills (p < 0.05). Agro Tani is feasible as a digital extension medium to support more accessible, flexible, and efficient agricultural information services at BPP Junrejo.